ANALISA PERILAKU MANAJEMEN TERHADAP PENERAPAN KOMPENSASI PROGRAM OPSI SAHAM EKSEKUTIF - Dr. Nur Fadjrih Asyik, M.Si. (EKUITAS (Jurnal Ekonomi dan Keuangan), 2007)
The purpose of this study is to investigate whether management who offer stock-based compensation which relatively big proportion to manage earnings information prior to grant date. While, this study also investigate the difference behavior of every step stock option offering. This paper contributes to that stream of accounting research by identifying several factors to manage earnings.The study finds that executives have ability to manage information around option grant date to find benefit stock price decreases before the grant date. Its show that the greater of stock option which granted to employee the more motive to manage decreasing earnings management prior to the grant date. The results are consistent with previous researchs that managers in the firms that offering the greater of stock option have the larger motivation to manage decreasing earnings so that can pay the stock option at the price of cheap (Chauvin & Shenoy, 2000; Baker et al., 2002; Balsam et al., 2003). While, based steps of stock option offering, the results of analysis show that there are the difference of influence of offer of the stock option on earnings management behavior at phase 1 and 2, while phase 3 do not differ from phase 1. The general conclusion is that magnitude of ESOP compensation effect earnings management behavior with supported by several conditional factors.